Traditional marketing system in Antigua : an economic analysis - Hope, Dianne L. (ISER Cave HillBB, 1991)
Examines the food marketing system in order to determine the place and importance of Traditional Marketing System (TMS) within it. Looks at the economic efficiency of the TMS, to determine how the system utilised its resources and whether it was exploitive. Evaluates the ability of the TMS to stimulate and/or respond to changes in the output sector and in consumer tastes. Concludes that the TMS played an important role in getting produce from producers to consumers.